83‐3: TE‐Type AMOLED Display with Wide Viewing Angle and Ultra‐Low Reflectance. Issue 1 (25th September 2020) - Abe, Kaoru; Taguchi, Tokio; Zhang, Bai; Yamane, Yu; Yasukawa, Kohji; Kawato, Shinichi; Mitsui, Seiichi
Abstract : AMOLED displays with highly viewing angle and ultra‐low reflectance have been developed. Using light diffusion film and Moth‐eye technology, which indicates.